1989
DOI: 10.1016/s0022-5347(17)39054-7
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium-To-Calcium Ratio in Tap Water, and its Relationship to Geological Features and the Incidence of Calcium-Containing Urinary Stones

Abstract: We examined the relationship among magnesium and calcium content in tap water, the geological features and urinary stone incidence in Japan. The magnesium-to-calcium ratio in tap water correlated negatively with the incidence of urolithiasis. There was no correlation between calcium and magnesium concentration in tap water and urinary stone incidence. Geological features in Japan were classified into 5 groups. The magnesium-to-calcium ratio in the basalt areas was higher than in the other areas, while ratio in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 8 publications
0
11
0
3
Order By: Relevance
“…Moreover, while the mineral water induced only changes which reduced risk, the same cannot be said for tap water. The finding that the mineral water is superior to tap water may partly be explained in terms of results published by Kohri et al [27] who found that the Mg/Ca ratio in drinking water was negatively correlated with the incidence of urolithia sis. In the present study the values of this ratio were 0.098 and 0.178 for tap and mineral waters, respectively (ta ble 1), suggesting that, on the basis of their study, the min eral water would indeed have a more beneficial stonereducing effect.…”
Section: Effect Of Mineral Water On Urolithiasismentioning
confidence: 92%
“…Moreover, while the mineral water induced only changes which reduced risk, the same cannot be said for tap water. The finding that the mineral water is superior to tap water may partly be explained in terms of results published by Kohri et al [27] who found that the Mg/Ca ratio in drinking water was negatively correlated with the incidence of urolithia sis. In the present study the values of this ratio were 0.098 and 0.178 for tap and mineral waters, respectively (ta ble 1), suggesting that, on the basis of their study, the min eral water would indeed have a more beneficial stonereducing effect.…”
Section: Effect Of Mineral Water On Urolithiasismentioning
confidence: 92%
“…Studies on the mineralogy of kidney stones and the crystallization processes are particularly important, in order to understand the possible environmental and metabolic factors cause form kidney stones. Early studies on the urinary calculi problem have highlighted various discoveries on composition, mineralogy, structure, processes of formation and geo-environmental factors that influence the formation of calculi (Ackermann, Baumann, Futterlaib, & Zingg, 1988;Bellizzi et al, 1999;Kohri et al, 1989). Major chemical constituents of calculi are calcium oxalate, calcium phosphate and urites and some of the major minerals are whewhellite, weddelite, apatite, podolite, uricite, and struvite (Nasir, Kassem, El-Sherif, & Fattah, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of Mg and Ca has also shown contrasting relations to urolithiasis. (Kohri et al, 1989(Kohri et al, , 1993. Negative correlations have revealed the importance of intake of Ca for the excretion of excess oxalates (Ackermann et al, 1988;Cauderella, Rizzoli, Buffa, Bottura, & Stefoni, 1998;Guttenbrunner, Gildsdrof, & Hildebrandt, 1989;Marangella, Vitale, Petrarulo, Rovera, & Dutto, 1996;Rodgers, 1997Rodgers, , 1998Sommariva, Rigatti, & Viola, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the recurrence of renal stones increased with the ingestion of hard water [34], and that people who drank water with a low Mg/Ca ratio had a higher incidence of urinary stone disease in Japan [35]. Similarly, Yanagawa et al [36] reported that the patients who drank the well-water, which was similar in content to that in the Japanese study, tended to develop urinary stones, which confirms the finding of Kohri et al [35].As compared with both tap and soft water, hard water was associated with a significant 50% increase of the urinary calcium concentration in the absence of changes of oxalate excretion; the calcium-citrate index revealed a significant threefold increase during ingestion of hard water as compared with respect to soft water, making the latter preferable even when compared with tap water. [37]Study suggests that, intake of soft water is preferable to hard water, since it is associated with a lower risk for recurrence of calcium stones.…”
Section: Type Of Drinking Watermentioning
confidence: 99%